Empirical Investigation of the Impact of Exports on Economic Growth: Evidence from Nigeria, 1980-2016 - Duru, Innocent.U.; Ezenwe, Uka (International Journal of Publication and Social Studies, 2020)
This study investigated the nexus between exports and economic growth in Nigeria from 1980 to 2016. The methodology utilized for this study was the Autoregressive Distributed Lag Bounds testing technique to cointegration. The short-run and long-run results revealed that export exerted a negative and insignificant relationship with economic growth in Nigeria. However, openness to trade had a negative relationship with economic growth in both the short-run and long-run. This result implies that efforts by the government through the Economic Recovery and Growth Plan (ERGP), which is an export-led economic growth and development agenda and the National Industrial Revolution Plan (NIRP) meant to revive the industries and possibly make manufactured exports a reality are not yielding the desired results. The causality results showed a uni-directional causality running from non-oil exports to economic growth. However, no causality was found between exports of goods and services and economic growth. The study, therefore, recommends that the government needs to diversify her export composition by finding a viable alternative to crude oil export. The government should implement policies that promote non-oil exports with a view to growing the economy. Moreover, the government should invest in technologies for the processing of primary export commodities to ensure value addition. Besides, a conducive climate is needed in the export sector to attract investors. Furthermore, subsidies should be provided by the government to export-oriented producers such as smallholder farmers and Small and Medium Scale Enterprises that motivate the economy.